Austro-German liberalism and Bohemian state rights, 1861-1879 - Kwan, Jonathan (Masaryk Institute and Archives of CAS, 2016)
This article aims to investigate the viewpoint of the Austro-German liberal movement – both ideologically and practically – towards the arguments for Bohemian state rights made by the conservative Bohemian Great Landowners and Czech political parties in the period from 1861 to 1879. The February Patent of 1861 is a convenient starting point because it reintroduced representative bodies and facilitated the development of modern democratic politics. The 1879 parliamentary elections constituted a significant turning point in Austrian and Bohemian politics since the Austro-German liberals lost the majority in the central parliament while the conservative Bohemian and Czech parties attended parliament after a sixteen-year absence and joined the conservative-Slav coalition supporting the government.